Literature Review and Conceptual Models Development on Public Services Motivation - Metha Djuwita Supriatna; Hafid Aditya Pradesa; Ramdani Priatna (Warmadewa Management and Business Journal (WMBJ), 2019)
Public Service Motivation (PSM) has become a basic important thing in employee’s self who work in a public sector organization. It has been previously recognized that behavioural researchers in organizational studies make efforts to develop a new set of motivational theories that only apply in the context of public organization. The purpose of this article is to identify the exploration of various things related to public service motivation. By using literature review, this study identifies preliminary empirical and theoretical literature that particularly discusses public services motivation, particularly for preliminary research including in the category of causality research (cause and effect). Some findings in this study reveal the positive effects of the antecedents of Public Services Motivation that is the most recognizable, which are personal characteristics, job characteristics, and employee perceptions about organization. Furthermore, the main outcome form of Public Services Motivation is attitudes (satisfaction and commitment) and individual behaviour (such as employee performance, turnover intention, and additional role behaviour-ex. OCB (Organizational Citizenship Behaviour)). The results obtained in preliminary empirical outcomes that are shown in the form of theoretical and empirical mapping about antecedents and outcomes of public service motivation, in which could be used as a strong empirical basis of depth study about public service motivation in the future.